2016
DOI: 10.1016/j.istruc.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of PVC encased reinforced concrete walls under eccentric axial loading

Abstract: Stay-in-place (SIP) formwork has been used as an alternative to the conventional formwork system. The systems are mainly assembled on site, hence simplifying the construction process and reducing the construction time as the removal procedure has been eliminated. SIP formwork systems can be divided into two main categories; structural and non-structural formwork, based on their contribution to resist applied loads.The structural formwork provides the same advantages as the non-structural formwork, in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The consumption of PVC is reported to be increasing, from around 40 million tons in 2013 by about 3.2% annually until 2021 [128,129]. The literature shows that most interest is in using PVC as coating or as a competitor to current fiber reinforced polymers (FRP) used due to its high durability, anti-corrosion, and strength to weight ratio [130][131][132]. Mohammed et al [133] and Kou et al [134] exercised the use of PVC as plastic aggregate, positively concluding, lower density and drying shrinkage and greater Poisson's ratio while added to concrete mixture.…”
Section: Polyvinyl Chloride (Pvc)mentioning
confidence: 99%
“…The consumption of PVC is reported to be increasing, from around 40 million tons in 2013 by about 3.2% annually until 2021 [128,129]. The literature shows that most interest is in using PVC as coating or as a competitor to current fiber reinforced polymers (FRP) used due to its high durability, anti-corrosion, and strength to weight ratio [130][131][132]. Mohammed et al [133] and Kou et al [134] exercised the use of PVC as plastic aggregate, positively concluding, lower density and drying shrinkage and greater Poisson's ratio while added to concrete mixture.…”
Section: Polyvinyl Chloride (Pvc)mentioning
confidence: 99%
“…are used as permanent formwork (Verbruggen et al, 2013(Verbruggen et al, , 2014VanderWerf, 2007). The use of permanent formwork for the construction of RC structures allows increasing their load-bearing capacity and significantly reducing the labor input (Scott et al, 2016;Havez et al, 2016). It is believed that a significant advantage of this TS is the minimum requirement of equipment for installation of formwork.…”
Section: Analysis Of the Stated Issuementioning
confidence: 99%
“…It was concluded that ALR has substantial effect on the deformability and failure mode of the walls and it was shown that an increase in ALR has adverse effects on strength degradation and energy dissipation of RC walls. As discussed by many researchers [14][15][16][17] stay-in-place (SIP) formworks, as permanent formworks for the concrete walls, are morepractical alternatives to traditional steel or wood formworks due to their improved constructability and durability. SIP formwork systems are mainly assembled on site, hence facilitating the construction process and decreasing the construction time as the removal procedure is eliminated.…”
mentioning
confidence: 99%
“…SIP formwork systems are mainly assembled on site, hence facilitating the construction process and decreasing the construction time as the removal procedure is eliminated. 15 Most of these systems are made of lightweight and prefabricated materials such as PVC and FRP. 16 Abdulla, 18 in a comprehensive study on PVC encased RC members, pointed out that more practical work, laboratory and field tests, and detailed information from analytical and experimental studies will be required for developing appropriate design guidelines for composite PVC encased RC members.…”
mentioning
confidence: 99%
See 1 more Smart Citation